Differential effects of PCSK9 inhibitors and statins on plasma ceramides in coronary artery disease - Zhang, Liang; Ding, Yaodong; Zeng, Yong (Frontiers in Pharmacology, 2025)
BackgroundWhile elevated plasma ceramides are independently associated with increased cardiovascular risk in patients with coronary artery disease (CAD), the impact of current lipid-modifying drugs on ceramides, remains under-researched. This study examines the effect of PCSK9 inhibitors on plasma ceramides in patients with CAD who had received statin therapy.MethodsComparing the effect of PCSK9i vs. statin on ceramide levels. The primary outcome was percent change in ceramide levels. Subgroup analyses were done to explore potential treatment effect differences.ResultsAmong 292 patients (44% statin group, 56% PCSK9i group), baseline characteristics were broadly similar. PCSK9i use significantly reduced ceramide levels compared to statin therapy: Cer 16:0 decreased by −22.93% (95% CI, −29.73% to −16.14%), Cer 18:0 by −24.54% (95% CI, −33.07 to −16.01), and Cer 24:0 by −34.82% (95% CI, −48.41 to −21.23). PCSK9i also significantly lowered LDL-C by 29.63%, triglycerides by 16.69%, and total cholesterol by 10.25%, while modestly increasing HDL-C. Sensitivity and subgroup analyses confirmed the consistent ceramide-lowering effect of PCSK9i across various patient demographics and baseline characteristics.ConclusionPCSK9i is associated with significant reduction in distinct ceramide concentrations, compared statin therapy only.